Do swimmers always perform better using their preferred technique? - Tor, E.; Pease, D.; Ball, K. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study compared four underwater trajectories in order to determine if swimmers will always perform fastest using their preferred technique. Fourteen elite swimmers were asked to dive at three depths as well as their preferred dive. These conditions were labelled as Dive 1, Dive 2, Dive 3 and Preferred. The Wetplate Analysis System was used to collect all data before descriptive statistics were determined. Inter-trial variability on a group basis revealed little difference in variance between each dive type. Further individual analyses found that seven of the fourteen swimmers performed faster using a non-preferred technique. In contrast to other studies which have found that swimmers will favour their preferred start technique there is evidence in this study to suggest that elite swimmers are able to readily change their underwater trajectory.